Targeting autophagy as a therapeutic strategy to prevent dopamine neuron loss in early stages of Alzheimer disease. Issue 5 (4th May 2021) - Nobili, Annalisa; La Barbera, Livia; D'Amelio, Marcello
ABSTRACT: Alzheimer disease (AD) is a neurodegenerative disorder for which no approved medication exists. AD is characterized by worsening cognitive and non-cognitive symptoms, and research in the AD field strives to identify very precocious brain alterations leading to an irreversible condition. Recently it has been demonstrated that several early AD symptoms are paralleled with degeneration of neurons producing dopamine (DA), a neurotransmitter involved in the regulation of cognitive and non-cognitive functions. Actually, we found that ventral tegmental area (VTA) DA neurons degenerate early in a validated AD mouse model (Tg2576). Here, we summarize new data showing how macroautophagy/autophagy impairment – due to enhanced activity of the ABL/c-Abl kinase – might cause the DA neuron loss. We also proved that nilotinib, an ABL inhibitor, restores autophagy flux, thus preventing VTA neurodegeneration. Most notably, from a clinical point of view, nilotinib, by preventing DA neuronal loss, preserves DA outflow in VTA-projecting areas, improving Tg2576 behavioral phenotypes. Our findings shed light on the mechanism involved in DA neurodegeneration, revealing that autophagy represents a viable therapeutic target in early AD.